Examples of holistic good practices in promoting and protecting mental health in the workplace: current and future challenges - Sivris, Kelly C.; Leka, Stavroula (Elsevier, 2015)
Background: While attention has been paid to physical risks in the work environment and the promotion of individual employee health, mental health protection and promotion have received much less focus. Psychosocial risk management has not yet been fully incorporated in such efforts. This paper presents good practices in promoting mental health in the workplace in line with World Health Organization (WHO) guidance by identifying barriers, opportunities, and the way forward in this area. Methods: Semistructured interviews were conducted with 17 experts who were selected on the basis of their knowledge and expertise in relation to good practice identified tools. Interviewees were asked to evaluate the approaches on the basis of the WHO model for healthy workplaces. Results: The examples of good practice for Workplace Mental Health Promotion (WMHP) are in line with the principles and the five keys of the WHO model. They support the third objective of the WHO comprehensive mental health action plan 2013e2020 for multisectoral implementation of WMHP strategies. Examples of good practice include the engagement of all stakeholders and representatives, science-driven practice, dissemination of good practice, continual improvement, and evaluation. Actions to inform policies/legislation, promote education on psychosocial risks, and provide better evidence were suggested for higher WMHP success. Conclusion: The study identified commonalities in good practice approaches in different countries and stressed the importance of a strong policy and enforcement framework as well as organizational responsibility for WMHP. For progress to be achieved in this area, a holistic and multidisciplinary approach was unanimously suggested as a way to successful implementation.